1986
DOI: 10.1111/j.1471-0528.1986.tb08656.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound assessment of cerebral blood flow in the human fetus

Abstract: A mechanical sector and linear array real-time scanner combined with a pulsed Doppler system was used for recording the flow velocity waveform in the internal carotid artery, the lower thoracic part of the descending aorta and umbilical artery in the human fetus. A total of 42 fetuses in normal pregnancy and nine growth-retarded fetuses between 26 and 41 weeks gestation was studied. In normal pregnancy the mean pulsatility index (PI) in the internal carotid artery varied between 1-5 and 1.6, in the descending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
14

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(104 citation statements)
references
References 11 publications
3
86
1
14
Order By: Relevance
“…24 The filters used in existing CTG monitors to remove baseline noise and improve heart rate recording prevent the detection of all but gross FECG waveform changes. An increase in the ST segment and T-wave of the fetal ECG in response to fetal hypoxia can be expressed as a ratio of T-wave height to QRS height (T/QRS ratio).…”
Section: Fetal Echocardiography (Fecg)mentioning
confidence: 99%
“…24 The filters used in existing CTG monitors to remove baseline noise and improve heart rate recording prevent the detection of all but gross FECG waveform changes. An increase in the ST segment and T-wave of the fetal ECG in response to fetal hypoxia can be expressed as a ratio of T-wave height to QRS height (T/QRS ratio).…”
Section: Fetal Echocardiography (Fecg)mentioning
confidence: 99%
“…4 As part of the circulatory response to hypoxia, a decrease of vascular flow resistance in the fetal middle cerebral artery (MCA) has then been demonstrated. 5,6 This redistribution of blood flow, a 'brain-sparing' effect, suggests an adaptation of the fetal circulation to hypoxemia. 5,6 In the human fetus redistribution of blood flow may be a response to chronic compromise rather than to an acute development of hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This redistribution of blood flow, a 'brain-sparing' effect, suggests an adaptation of the fetal circulation to hypoxemia. 5,6 In the human fetus redistribution of blood flow may be a response to chronic compromise rather than to an acute development of hypoxemia. During the first stage of labor and in the absence of fetal distress, Maesel et al 7 found no significant changes of fetal MCA blood flow in association with uterine contractions.…”
Section: Introductionmentioning
confidence: 99%
“…The absence and reversal of end-diastolic flow (ARED) in the umbilical arteries of these fetuses were amazing demonstrations of fetal pathophysiology. 41 The Publishing his results as early as 1989, Asim Kurjak, using the Aloka ® machine, was the first to apply transvaginal color Doppler for studies of the pelvic circulation. 42 In the same year, Toshiyuki Hata and co-workers (Japan) did publish about "Transvaginal Doppler color flow Mapping".…”
mentioning
confidence: 99%